Penerapan Environmental, Social, dan Governance (ESG) Pada Program Insfrastruktur Di Indonesia: Menuju Sustainable Business - Muhammad Fachrizal Wahyu Darma Putra; Nurul Asfiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Social, environmental, and governance issues are crucial for businesses today. Companies need to report their environmental concern activities in Environmental, Social, and Governance (ESG) reports. This research aims to understand the implementation of ESG in infrastructure programs in Indonesia. It employs a bibliometric approach based on international publication data sourced from the Google Scholar database, accessed via Harzing’s Publish or Perish. The findings of this study indicate that ESG serves as a fundamental framework for infrastructure companies in Indonesia to guide sustainable business practices. By integrating environmental, social, and governance aspects, companies can act as agents of positive change in society.